2020
DOI: 10.1016/j.isci.2020.101389
|View full text |Cite
|
Sign up to set email alerts
|

HASLR: Fast Hybrid Assembly of Long Reads

Abstract: Summary Third-generation sequencing technologies from companies such as Oxford Nanopore and Pacific Biosciences have paved the way for building more contiguous and potentially gap-free assemblies. The larger effective length of their reads has provided a means to overcome the challenges of short to mid-range repeats. Currently, accurate long read assemblers are computationally expensive, whereas faster methods are not as accurate. Moreover, despite recent advances in third-generation sequencing, res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 44 publications
(86 reference statements)
0
34
0
Order By: Relevance
“…The short-read genomic data were also screened with these reference sequences using the bbduk tool in bbmap, and then normalized using bbnorm. With these refined read sets, we generated a final assembly using the hybrid assembler haslr (Haghshenas et al, 2020).…”
Section: Genome Assembly Decontamination and Genome Assessmentmentioning
confidence: 99%
“…The short-read genomic data were also screened with these reference sequences using the bbduk tool in bbmap, and then normalized using bbnorm. With these refined read sets, we generated a final assembly using the hybrid assembler haslr (Haghshenas et al, 2020).…”
Section: Genome Assembly Decontamination and Genome Assessmentmentioning
confidence: 99%
“…We compare results to the most widespread competing assembler Canu [ 10 ] and the faster Wtdbg2 [ 13 ], both demonstrating the disadvantages of long-read-only strategies especially in low coverage scenarios, although Wtdbg2 requires considerately less coverage in comparison. Additionally, we benchmarked two tools implementing the most closely related concept: DBG2OLC [ 23 ] and most recent competitor HASLR [ 21 ]. Finally, we added Wengan [ 19 ] as a leading but conceptually very unique alternative.…”
Section: Benchmarkingmentioning
confidence: 99%
“…HASLR [ 21 ] defines an assembly-graph-like structure, that includes both short and long reads. Short reads are assembled into contigs that, after k -mer filtering to remove repeats, are aligned to long reads.…”
Section: Introductionmentioning
confidence: 99%
“…[14]. Hybrid (HY) assembly methods [15,16] using both SRs and LRs have been proposed to further reduce the error rates compared to LR-only assemblies. While Watson et al [14] showed that insertions/deletions (indels) play a critical role in microbial protein identification, the overall impact of assembly methods on understanding the functional potential of microbial communities is lacking.…”
Section: Introductionmentioning
confidence: 99%